The Effect of Change Management and Adaptation on Employee Performance at PT. Frisian Flag Indonesia Jakarta - Pawit Winarto; Haryanto Haryanto (Journal of Business, Management, & Accounting, 2023)
This study aims to identify and analyze the relationship between change management and adaptation to the performance of PT. Frisian Flag Indonesia, Jakarta. The research data was collected by distributing questionnaires with a total sample of 86 respondents and using a descriptive quantitative approach. The analysis used is statistical analysis in the form of multiple linear regression testing. The test results show that there is a positive and significant influence between change management and adaptation on the performance of employees of PT. Frisian Flag Indonesia. It is also proven from the results of the F test that the significance values ​​of the two independent variables support the research hypothesis